Building the Attitude of Consumer Concern for Environmentally Friendly Products - Renny Risqiani; Siti Maemunah (Business and Entrepreneurial Review, 2016)
This study aims to determine what factors can influence consumer attitudes on green products (attitude on green product). Furthermore, it will be analyzed whether consumer attitudes on green products have an effect on green behavior intention, the influence of green behavior intention towards the green purchase behavior. The sampling technique using purposive sampling of 220 students in the Jakarta area. The data analysis method used in this study is to use Structural Equation Modeling (SEM). The results of this study are consumer attitudes towards green product influenced by social influence and personal norms. While government roles, environmental emotion and cognition have no significant effect. The higher the consumer's attitude towards the green product, the more it increases consumer attitudes to care about the environment and will have an impact on purchasing behavior towards environmentally friendly products